Kinerja Produksi Ikan Sidat (Anguilla Bicolor Bicolor) dengan Volume Air Pemeliharaan yang Berbeda pada Sistem Resirkulasi - Eko Harianto; Eddy Supriyono; Tatag Budiardi; Ridwan Affandi; Yani Hadiroseyani (Universitas Batangahari Jambi, 2022)
Eel (Anguilla bicolor bicolor) rearing activities that develop in Indonesia generally still use a large volume of water. The application of a recirculation system reduces water requirements and at a small volume of water, the load on the container to accommodate water becomes lighter so that several containers can be arranged vertically. This study aims to determine the best water volume in eel rearing with a recirculation system on production performance. This study used a completely randomized design with four treatments and three replications. The treatments, namely the difference in the volume of water (VA) used in the maintenance container, included VA 2.5 L (A), VA 3.5 L (B), VA 4.8 L (C) and VA 5.8 L (D). Eels were reared for 60 days in an aquaverticulture system with a stocking density of 10 fish per container. The test parameters in this study included survival rate (SR), specific growth rate (LPS), absolute weight growth (PBM) and feed conversion (FCR) and coefficient of final weight diversity (KKb). Other parameters analyzed include water and land use analysis. The results showed that aquaverticulture with multilevel containers on eel produced the best water volume of 5.8 L with high production performance (100% survival, specific growth rate 1.60%/day). The volume of water needed to produce 1 kg of eel for 1 year is 27.69 liters and the productivity of aquaculture land is 86.14 kg/m2. During the COVID-19 pandemic, this system design has been applied on a laboratory scale, but has not been applied commercially in the community.